A dual role of microbiota type 17 immunity in tissue repair and pain. Issue 4 (9th March 2023) - Austin, Paul J; Karrasch, Jackson F; O'Brien, Jayden A
Abstract : In this commentary, we discuss the findings of Enamorado et al. who have, for the first time, demonstrated that immunity to the microbiota enhances repair of cutaneous sensory nerves and epithelial tissues following skin injury. Commensal‐specific IL‐17 producing CD4 + T helper cells have direct contact with injured sensory neurons, inducing multiple epithelial and neuronal repair genes. We speculate that an altered balance of T cell populations in the skin of people with chronic neuropathic pain may contribute to a reduction in neuronal repair and the consequent decease in intraepidermal nerve fibre density and persistent pain.